Fatores psicossociais e saúde mental relacionados ao contexto de trabalho do docente de ensino fundamental - Tatsch, Sabrina (My University, 2025)
Elementary school teachers represent a significant portion of education professionals in Brazil. The changes that have occurred over the years in education, with educational reforms and restructuring of teaching, have led to an intensification of teaching work, putting the health of these workers and the quality of education at risk. The teaching profession is considered by the International Labor Organization (ILO) as one of the most stressful in the world. Work-related stress can be caused by psychosocial factors at work that affect the psychological state and social relationships of people in organizations and influence the overall health of workers. This research analyzed the psychosocial factors at work (risk and protection) that influence the mental health of teachers in the context of elementary school organizations. The method used was a mixed sequential explanatory cross-sectional approach. The quantitative research was conducted using the Health Safety Executive - Indicator Tool - HSE-IT and the qualitative research was conducted using focus groups. The participants were teachers from the initial and final years of elementary school in a medium-sized city in the interior of Rio Grande do Sul. The results from the quantitative analysis showed that the dimensions "demand", "control", and "leadership support" were scored as having the highest risk factor for stress, although with percentages below 30.20% and without statistically significant difference. The dimensions "support from colleagues", "position", "relationships" and "communication and changes" presented a lower risk factor for stress, not exceeding the percentage of 8.70% and also without statistically significant difference. The results from the qualitative analysis derived from the focus groups showed psychosocial protective factors in teaching work, such as: "support from colleagues", "leadership support", "healthy school environment", "socio-emotional skills", "identification", "self-efficacy", "appreciation" and "reward". On the other hand, there are also psychosocial risk factors, such as: "excessive demands", "precarious support", "negative effects of teaching stress", "her training" and "precarious leadership development". It is understood that this study can contribute to fostering debate and achieving greater awareness, generating prevention actions that enhance the factors that protect teachers' mental health and reduce risks, in addition to contributing to the strengthening of healthy school organizations. Finally, the contribution of this research is the development of two technical products: Multimedia pedagogical resource: "Psychosocial factors in the context of teaching work" and the proposal of a mandatory curricular subject for undergraduate courses: "Psychosocial factors in the context of teaching work" with the aim of promoting scientific knowledge and contributing to practices for preventing teacher illness and promoting mental health. [resumo fornecido pelo autor]
Os docentes do Ensino Fundamental representam uma significativa parcela dos profissionais da educação no Brasil. As mudanças que vêm ocorrendo ao longo dos anos na educação, com reformas educacionais, reestruturação do ensino, geraram uma intensificação do trabalho docente colocando em risco a saúde desses trabalhadores e a qualidade da educação. A profissão docente é considerada pela Organização Internacional do Trabalho (OIT), como uma das mais estressantes a nível mundial. O estresse laboral pode ser decorrente dos fatores psicossociais do trabalho que afetam o estado psicológico e as relações sociais das pessoas nas organizações e influenciam a saúde integral do trabalhador. Esta pesquisa analisou os fatores psicossociais do trabalho (de risco e de proteção) que influenciam na saúde mental do docente no contexto da organização escolar de Ensino Fundamental. O método utilizado foi misto de abordagem sequencial explanatória transversal. A pesquisa quantitativa se deu através do instrumento Health Safety Executive - Indicator Tool- HSE-IT e a pesquisa qualitativa por meio de grupos focais. Os participantes foram docentes dos Anos iniciais e dos Anos finais do Ensino Fundamental de um município de médio porte do interior do Rio Grande do Sul. Os resultados decorrentes da análise quantitativa evidenciaram que as dimensões "demandas", "controle", "apoio da chefia" foram pontuadas com maior fator de risco de estresse, embora com percentuais abaixo de 30,20% e sem diferença estatisticamente significativa. As dimensões "apoio dos colegas", "cargo", "relacionamentos" e "comunicação e mudanças" apresentaram menor fator de risco de estresse, não ultrapassando o percentual de 8,70% e sem diferença estatisticamente significativa. Os resultados da análise qualitativa derivada dos grupos focais evidenciaram fatores psicossociais de proteção no trabalho docente, tais como: "apoio dos colegas, "apoio da chefia", "contexto saudável da escola", "competências socioemocionais", "identificação" "autoeficácia", "valorização" e "recompensa". Em contrapartida, há também a existência de fatores psicossociais de risco, como: "excesso de demandas", "apoio precário", "efeitos negativos do estresse docente", "normalização da precarização do trabalho docente", "carência de conhecimentos sobre fatores humanos na formação docente" e "desenvolvimento da liderança precário". Entende-se que o presente estudo possa contribuir para fomentar o debate e alcançar uma maior consciência, gerando ações de prevenção que potencializem os fatores de proteção à saúde mental dos docentes e a redução dos riscos, além de favorecer para o fortalecimento de organizações escolares saudáveis. Por fim, a contribuição dessa pesquisa é a elaboração de dois produtos técnicos: o recurso pedagógico multimídia "Fatores psicossociais no contexto de trabalho docente" e a proposta de uma disciplina curricular obrigatória para os cursos superiores de licenciatura com o título "Fatores psicossociais no contexto de trabalho docente". O intuito desses produtos técnicos é promover o conhecimento científico e fomentar práticas de prevenção ao adoecimento docente e promoção da saúde mental. [resumo fornecido pelo autor]
Keywords: Psicologia social; Professores - Saúde mental; Trabalho - Aspectos psicológicos; Ensino fundamental - Brasil; Doenças profissionais; Promoção da saúde dos empregados; Social psychology; Teachers - Mental health; Work - Psychological aspects; Elementary school - Brazil; Occupational diseases; Employee health promotion